Reparative complementarity in international criminal law and victims of core international crimes in Nigeria (2020)
The Rome Statute of the International Criminal Court evinces a victim- centred concept through the provisions of Article 75, by providing reparations to victims in addition to prosecutions of perpetrators. On the other hand, the operation of the International Criminal Court is built upon the principle of complementarity, which gives primacy to jurisdictions of domestic courts in prosecuting core international crimes over the ICC. Reparations are important to victims, in fact, it may appear that victims who participate in criminal proceedings do so with the aim of getting more than just prosecution of the perpetrators, but much more reparative remedy The concept and practice of reparations at the ICC, especially in the reparation decisions thus Jar, has its own peculiar challenges. Despite the challenges relating to the practice of reparation at the ICC, there is a growing concern as to whether victims have a right to seek reparations from their States and whether States in turn have the obligation of providing reparations to victims following the principle of complementarity. Thus, are Slate parties obliged to incorporate reparations in line with domestic prosecution of core international crimes in fulfilment of their obligations to prosecute? Assuming Stales parties are obliged, what would the principle of ‘reparative complementarity' portend for a country’ like Nigeria where the concept of reparations to victims in criminal law context, appears alien? The paper interrogates the above questions and others in the light of the hundreds of thousands of displaced victims of the insurgency and armed conflicts in the country. The paper adopts a doctrinal and library based approach to examine the concept of reparative complementarity and its practical application to Nigeria's obligations to victims of crime in international criminal law. The paper argues Jar a variant of reparative complementarity which distils two main perspectives of State obligation in reparative complementarity and advocates for a more victim centred approach to criminal justice in Nigeria.